SENSORLESS OPTIMAL CONTROL OF A FIVE-PHASE INDUCTION MOTOR WITH HARMONIC MINIMIZATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This work presents a sensorless optimal control strategy (model predictive torque and speed control) applied to a five-phase induction machine. Model predictive control (MPC) is used for both torque and flux control, eliminating the need for traditional field-oriented control (FOC) and direct torque control (DTC) techniques. Additionally, model predictive speed control (MPSC) replaces the conventional PI regulator, ensuring fast response and improved dynamic performance. An extended Kalman filter (EKF) is integrated, allowing for accurate estimation of rotor flux, stator currents, and speed. The components of Clarke currents that contribute to harmonic generation are incorporated into the model-predictive torque control (MPTC) optimization criterion. The simulation results from MATLAB Simulink demonstrate the effectiveness of this strategy.
Keywords: Model predictive torque and speed control; Sensorless optimal control; Extended Kalman filter; Five-phase induction machine; Harmonic minimization